Effect of the HBV Capsid Assembly Inhibitor Bayer 41-4109 on the Intracellular Localization of EGFP-Core Fusion Proteins - Haryanto, Aris; Wijayanti, Nastiti; Kann, Michael (Universitas Gadjah Mada, 2007)
Bayer 41-4109 is heteroarylpyrimidine (HAP) which has been identified as potent of HBV capsid assemblyinhibitor. The present study was to study effect of Bayer 41-4109 treatment on the intracellular localization ofEGFP-Core fusion proteins into HepG2 cells. Three recombinant plasmids of pEGFP-Core with single, double andtriple NLS of HBV core (EGFP-Core 1C, 2C and 3C ) and two recombinant plasmids with single and triple NLS ofSV-40 (EGFP-Core 1 and 3 SV-40) were used in this work. After transient transfected into HepG2 cells and treatedwith Bayer 41-4109, the intracellular localization of expressed fusion proteins from all plasmid constructions weredetermined and quantified under confocal laser microscope. Results shown that Bayer 41-4109 treatment in HepG2cells inhibited the nuclear localization of EGFP-Core with single of triple HBV core NLS. As well as the constructionsof expressed fusion protein with single and triple SV-40 NLS (EGFP-Core 1 and 3 SV-40 NLS) showeddecreasing the nuclear localization after treated with Bayer 41-4109, even not as strong as EGFP-Core 1C and 3CNLS. Bayer 41-4109 has been identified as a potent inhibitors of HBV replication which has multiple effects on HBVcapsid assembly. It may inhibit virus replication by inducing assembly inappropriately and by misdirectingassembly decreasing the stability of normal capsids.Keywords: HBV capsid, Bayer 41-4109, EGFP-Core fusion protein, HepG2 cell